The new face of evaluation and management : a guide to calculating E/M CPT codes through best practice documentation - Hall, Kellie S. (Productivity Press, 2025)
Physicians want to care for patients, not spend their time documenting in an electronic medical record. Physicians are always complaining about the amount of time they spend documenting patient care in support of medical billing through an evaluation and management coding system (E/M). New guidelines were created to lessen the time a physician/provider spends on documentation as many of the mandatory elements are no longer a requirement for calculating a code level. Previously an E/M (evaluation and management) note required documentation of history, exam, and medical decision-making with required elements in each component to support a level for payment. If an element was missing, the level of service was not supported; therefore, the code was lowered, resulting in a lower reimbursement for the physician/provider. The new guidelines eliminated the requirement of History and Exam as part of the calculation of a code level. Yes, an appropriate history and exam are required, this supports good patient care, but when it comes to reimbursement, they are no longer part of the picture. The overall system is not difficult, if time is taken to understand the elements and how they are applied in the documentation. Documentation is a "word game" always has been, the authors' focus is to show what words to use to lessen the time but still convey the complexity of the patient's condition, and how the physician/provider determines a treatment plan which includes the risk to the patient to satisfy the Coding guidelines initiated by Medicare and American Medical Association. This book evaluates the new guidelines and brings them into prospective so physicians/providers/coders can easily understand how to document and calculate the level of service for reimbursement. This is not a cumbersome book or complicated, but straight to the point. The main goal of the book is to educate physicians, nurses, and coders on what documentation is really required and what has just become habit over the last 30 years.
Keywords: Medical codes.; Medical records -- Data processing.; Medical history taking.; elektronické knihy; electronic books